Penyuluhan deteksi dini stroke dengan metode FAST pada lansia - Istichomah Istichomah; I Putu Juni Andika (Jurnal Pengabdian Harapan Ibu (JPHI), 2022)
According to data from Each year, there are 12.2 million new strokes worldwide, and 101 million people live with a stroke after it. One in four people will have a stroke in their lifetime, a rate that has increased by 50% over the past 17 years. The World Stroke Organization (WSO) in 2022 is the only global body that focuses solely on stroke. Comprehensive efforts to manage stroke risk factors in the community should be pursued. Understanding stroke prevention and detection is very helpful in minimizing the effects of stroke. Health education about early detection of stroke using the FAST method is given to the elderly who have a high risk of stroke. Early detection of stroke using the FAST (Face drooping Arm Weakness Speech difficulty, Time to call doctor/hospital) method can be a solution to knowledge in an effort to prevent the impact of stroke. The activity, which was attended by 50 elderly people, ran smoothly and enthusiastically. The results of the evaluation revealed that there was a significant increase in good knowledge from 6% to 74%.